A Phenomenological Study of Lab-Scale Tidal Turbine Loading under Combined Irregular Wave and Shear Flow Conditions - Matthew Allmark; Rodrigo Martinez; Stephanie Ordonez-Sanchez; Catherine Lloyd; Tim O’Doherty; Grégory Germain; Benoît Gaurier; Cameron Johnstone (Journal of Marine Science and Engineering, 2021)
Tidal devices are likely to faced with shear flows and subjected to various wave climates. The paper presents an experimental study of the combined impacts of shear profile and irregular waves on the loading of a 1/20th scale device operating at peak power extraction. The experiments presented were conducted at various depths to facilitate analysis of the effects of the shear flow and wave impact on the device at various positions in the water column. The fluid field was measured at three different upstream positions and at three depths (top, middle and bottom of the rotor) for each experiment; in doing so, data from the device were captured three times. The fluid measurements were of a high quality and were analysed to present the structure flow upstream of the device, which contained velocity and turbulence profiles. The upstream measurement was utilised to understand the development of flow structures in the approach to the device, and the impact of the flow structures measured was confirmed via cross-covariance calculations. The long datasets gathered were used to produce full rotational probability density functions for the blade-root-bending moments for three blades. The spectral characteristics were also considered, and showed that rotor loading quantities are less reactive to smaller scale flow structures.